Researching Vulnerable Groups: Definitions, Controversies, Dilemmas, and the Researcher’s Personal Entanglement - Urszula Kluczyńska; Anna Maria Kłonkowska; Małgorzata Bieńkowska (Qualitative Sociology Review, 2024)
The article aims to describe vulnerable groups in the context of qualitative research in social science with special attention to ethical and methodological dilemmas. This is a theoretical study, which does not aspire to offer solutions or guidelines, but rather show elements worth taking notice of and analyzing when research is planned and carried out. We argue that in the social sciences, vulnerability is relational and crucial. However, social science researchers perceive the category of vulnerability as ambiguous and nuanced. This article shows that ascribing research participants univocally to a vulnerable group may lead not only to them being stereotyped and deprived of individuality but also to a situation where the research act itself disempowers them. We also argue that apart from issues often raised concerning the protection of participants from vulnerable groups, the researcher and their protection are also pivotal, particularly when the researcher, due to their involvement, abandons the out-group perspective or when they belong to the vulnerable group.